Analisis Penerapan Relationship Maintenance Strategy Melalui Penggunaan Media Sosial (Studi Pada Twitter Perbankan di Indonesia) - Rahmatul Jannatin Naimah; M. Riza Firdaus; Ahmad Rifani (Universitas Lambung Mangkurat, 2013)
Nowadays, banks are actively using twitter in order to maintain relationships with customers. Unfortunately, the trend of using social media as Relationship Maintenance Strategy (RMS) for the banking industry is not supported by adequate research in the realm of marketing public relation science. Positivity, openness, task sharing, networking, access, and assurance are six dimensions that can be used to measure the application of RMS through twitter. Thus, this research aims to analyze whether there are differences in the implementation of RMS in the Indonesia Banking Industry through content analysis of its official twitter. The banks that will be further investigated are the three top banks belonging to Indonesia Bank Loyalty Index (IBLI) and Most Followed Bank (MFB). Research findings resulted Banks belonging to IBLI and MFB group has a different level implementation of RMS through twitter. The overall level of implementation were found in two groups are still very low, especially in the task sharing dimension. IBLI banks more implement the dimension of RMS than MFB bank group. Assurance was most widely used on the two banking groups.